2012
DOI: 10.7326/0003-4819-156-8-201204170-00397
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Steroids, Etanercept, or Saline in Subacute Sciatica

Abstract: Agency for Healthcare Research and Quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
97
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 0 publications
1
97
0
Order By: Relevance
“…We identified seven RCTs [19][20][21][22][23][24][25][26] one non-RCT [27,28] and one historical cohort study [29]. Two studies were reported in two separate publications each [23,24,27,28].…”
Section: Description Of Biological Agents Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…We identified seven RCTs [19][20][21][22][23][24][25][26] one non-RCT [27,28] and one historical cohort study [29]. Two studies were reported in two separate publications each [23,24,27,28].…”
Section: Description Of Biological Agents Studiesmentioning
confidence: 99%
“…One RCT compared subcutaneous injection of etanercept with a placebo injection of saline [25], and another RCT compared three different doses of an epidural injection of etanercept with each other and with an epidural saline injection [20]. One three-armed RCT compared epidural injections of etanercept with epidural injections of corticosteroid and with epidural injection of saline [26].…”
Section: Description Of Biological Agents Studiesmentioning
confidence: 99%
See 3 more Smart Citations